2022
DOI: 10.1038/s41467-022-34932-z
|View full text |Cite
|
Sign up to set email alerts
|

GhostKnockoff inference empowers identification of putative causal variants in genome-wide association studies

Abstract: Recent advances in genome sequencing and imputation technologies provide an exciting opportunity to comprehensively study the contribution of genetic variants to complex phenotypes. However, our ability to translate genetic discoveries into mechanistic insights remains limited at this point. In this paper, we propose an efficient knockoff-based method, GhostKnockoff, for genome-wide association studies (GWAS) that leads to improved power and ability to prioritize putative causal variants relative to convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…This is a salient advantage of our proposed methodology compared to the original GhostKnockoffs method, which conducts similar conditional independence tests with marginal association test statistics. 20 Existing fine-mapping methods calculate relative likelihoods of causality using the PIP. 10 Interpretations of PIP calculated through different methods can be inconsistent, lacking a systematic approach to defining a cutoff for determining causal variants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is a salient advantage of our proposed methodology compared to the original GhostKnockoffs method, which conducts similar conditional independence tests with marginal association test statistics. 20 Existing fine-mapping methods calculate relative likelihoods of causality using the PIP. 10 Interpretations of PIP calculated through different methods can be inconsistent, lacking a systematic approach to defining a cutoff for determining causal variants.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming we generate 𝑀 knockoff copies, He et al ( 2022) 20 showed that one can generate knockoff feature importance measure according to a Z-score test by…”
Section: Conditional Independence Test Via Ghostknockoffsmentioning
confidence: 99%
See 3 more Smart Citations